Three‐Dimensionally "Curved" NiO Nanomembranes as Ultrahigh Rate Capability Anodes for Li‐Ion Batteries with Long Cycle Lifetimes. Issue 4 (10th October 2013) - Sun, Xiaolei; Yan, Chenglin; Chen, Yao; Si, Wenping; Deng, Junwen; Oswald, Steffen; Liu, Lifeng; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> Three‐dimensionally "curved" NiO nanomembranes made using a simple fabrication technique followed by a thermal oxidation process are reported. As anode materials for lithium ion batteries, the curved NiO nanomembranes exhibit impressive results, i.e., ultrafast power rate (50 C), a high capacity of 721 mAh g−1 at 1.5 C, and a long lifetime of 1400 cycles, making them attractive for high power Li‐ion batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>